Restrictions in Development of Rural Areas Resulting from Defective Structure of Cadastral Parcels - Delnicki, Maciej; Bielska, Anna; Turek, Agnieszka (Geomatics and Environmental Engineering, 2019)
Rural areas have been subjected to constant transformations for centuries. The current state of the settlement network and image of Polish space has resulted from a number of political and legal transformations along with economic and social processes. With the development of civilization, the factors determining the location of new residential building developments and the function of rural areas have changed. The importance of non-agricultural production functions and consumption functions has currently increased at a cost of a declining share of agricultural production. The objective of the study was to determine the degree to which the structure of cadastral parcels restricts the possibilities of development of different functions in rural areas. The research was conducted in the Nasielsk commune. Planning documents were analyzed to determine the directions of development of the commune. The structure of all of the commune´s cadastral parcels was analyzed to determine their surface areas and shapes. The layout of selected agricultural farms was determined, with a consideration for the area of the farms, the number of parcels, their surface areas, and their shapes. According to the research, the defective structure of cadastral parcels largely restricts not only the development of agriculture but also the rational management of parcels allocated for building development. Moreover, it facilitates a natural forest succession, which is favorable from an environmental point of view but undoubtedly constitutes an obstacle in the use of arable land.